Electrocardiographic Risk Stratification in COVID-19 Patients - Chorin, Ehud; Dai, Matthew; Kogan, Edward; Wadhwani, Lalit; Shulman, Eric; Nadeau-Routhier, Charles; Knotts, Robert; Bar-Cohen, Roi; Barbhaiya, Chirag; Aizer, Anthony; Holmes, Douglas; Bernstein, Scott; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: the COVID19 pandemic has resulted in worldwide morbidity at unprecedented scale. Troponin elevation is a frequent laboratory finding in hospitalized patients with the disease, and may reflect direct vascular injury or nonspecific supply-demand imbalance. In this work, we assessed the correlation between different ranges of Troponin elevation, Electrocardiographic (ECG) abnormalities and mortality. Methods. We retrospectively studied 204 consecutive patients hospitalized at NYU Langone Health with COVID19. Serial ECG tracings were evaluated in conjunction with laboratory data including Troponin. Mortality was analyzed in respect to the degree of Troponin elevation and the presence of ECG changes including ST elevation, ST depression or T wave inversion. Results. Mortality increased in parallel with increase in Troponin elevation groups and reached 60% when Troponin was >1 ng/ml. In patients with mild Troponin rise (0.05 – 1.00 ng/ml) the presence of ECG abnormality resulted in significantly greater mortality. Conclusion. ECG repolarization abnormalities may represent a marker of clinical severity in patients with mild elevation in Troponin values. This finding can be used to enhance risk stratification in patients hospitalized with COVID19.